2011
DOI: 10.7589/0090-3558-47.3.673
|View full text |Cite
|
Sign up to set email alerts
|

SEROEPIDEMIOLOGY OF TmPV1 INFECTION IN CAPTIVE AND WILD FLORIDA MANATEES (TRICHECHUS MANATUS LATIROSTRIS)

Abstract: ABSTRACT:In 1997, cutaneous papillomatosis caused by Florida manatee (Trichechus manatus latirostris [Tm]) papillomavirus 1 (TmPV1) was detected in seven captive manatees at the Homosassa Springs Wildlife State Park, Florida, USA, and, subsequently, in two wild manatees from the adjacent Homosassa River. Since then, papillomatosis has been reported in captive manatees housed in other locations, but not in wild animals. To determine TmPV1 antibody prevalence in captive and wild manatees sampled at various locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A few pilot studies have been conducted previously on Antillean manatees to determine hematology and biochemical reference intervals, but sample sizes were limited, and one of these studies was restricted to captive manatees [1], [19], [38], [39]. In the Florida subspecies, normal blood parameters have been documented in healthy free-ranging and captive manatees [27], [40], [41] along with preliminary seroprevalence data [42], [43]. Our study is the first large-scale effort to establish hematology and biochemistry reference intervals in healthy, wild Antillean manatees and report on baseline pathogen exposure in this subspecies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few pilot studies have been conducted previously on Antillean manatees to determine hematology and biochemical reference intervals, but sample sizes were limited, and one of these studies was restricted to captive manatees [1], [19], [38], [39]. In the Florida subspecies, normal blood parameters have been documented in healthy free-ranging and captive manatees [27], [40], [41] along with preliminary seroprevalence data [42], [43]. Our study is the first large-scale effort to establish hematology and biochemistry reference intervals in healthy, wild Antillean manatees and report on baseline pathogen exposure in this subspecies.…”
Section: Discussionmentioning
confidence: 99%
“…Indications of lowered immunity and increased susceptibility to infection in the Florida subspecies became apparent with the discovery of a novel, manatee-specific papillomavirus in 1997 [43], [63], [64]. In general, the number of infectious agents discovered in marine mammals has risen over the past two decades [10], [65].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no publicly available sequence information for either Asian or African savanna elephant α constant regions. Very little specific information is known regarding immunoglobulin genes in other members of the Afrotheria superorder, although there has been specific antisera generated towards IgG in manatees ( Sirenia ) and identification of cross-reacting commercial antisera towards IgG in elephant shrews ( Macroscelidea ) and hyraxes ( Hyracoidea ) [ 15 , 16 ]. In order to address some gaps in our understanding of elephant immunoglobulin isotypes, we sought to determine whether Asian elephants produce IgM or IgA and to use this information to generate or identify specific antibodies that could detect these immunloglobulin isotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, clinicoimmunologic data suggest that the manatees with cutaneous tumours associated with TmPV1 are immunologically suppressed and that the papillomas result from activation of latent papillomavirus infections and re-inoculation from active infections [20]. Additionally, recent seroepidemiologic data [33] indicated that Florida manatees living in the wild are naturally infected by TmPV1 but rarely show TmPV1-induced papillomatosis. The prevalence of TmPV1 antibody among manatees with the absence of lesions suggests an immunologic response that effectively controls productive PV infection and/or rapidly resolves lesions.…”
Section: Papillomavirusesmentioning
confidence: 99%